A porous Fe for lithium ion battery 2 O 3 @Mn 2 O 3 Core-shell cubic structure material and preparation method thereof

The porous Fe2O3@Mn2O3 core-shell cubic structure electrode material was prepared by one-step hydrothermal method, which solved the problems of low specific capacity and unsafe working potential of the existing lithium-ion battery anode material, and achieved electrochemical performance with high specific capacity, good rate performance and cycle stability. It was suitable for lithium-ion battery anode material.

CN119284968BActive Publication Date: 2025-03-18SOUTHWEST PETROLEUM UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411786971.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-18
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have problems such as low specific capacity, unsafe working potential, slow electrochemical kinetics, and poor rate performance, which limit the cycle life and safety of lithium-ion batteries.

Method used

The porous Fe2O3@Mn2O3 core-shell cubic structure material was prepared by one-step hydrothermal method. The molar ratio of Fe(NO3)3·9H2O and MnSO4·H2O was 1:1, the molar ratio of Fe(NO3)3·9H2O and CH4N2O was 1:10, the hydrothermal reaction temperature was 140-160℃, the time was 10 hours, the stirring speed was 600rpm, the pressure was 3-4MPa, and finally the porous Fe2O3@Mn2O3 core-shell cubic structure electrode material was sintered at 800℃.

Benefits of technology

The prepared porous Fe2O3@Mn2O3 core-shell cubic structure electrode material has high specific capacity, good rate performance and cycle stability. It shows excellent electrochemical performance as a negative electrode material for lithium-ion batteries, and has rich raw material reserves, low price, and simple and easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119284968B_ABST
    Figure CN119284968B_ABST
Patent Text Reader

Abstract

The present invention discloses a porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium ion batteries and a preparation method thereof, and belongs to the technical field of lithium ion battery electrode materials. The preparation steps of the present invention are as follows: (CH2OH)2 is added to deionized water and stirred evenly, and then Fe(NO3)3·9H2O, MnSO4·H2O and CH4N2O are added to an ethylene glycol aqueous solution and stirred evenly, and then heated and stirred in a pressure reactor and subjected to a hydrothermal reaction, and then taken out and cooled to room temperature, and the obtained precipitate is centrifugally washed several times with anhydrous ethanol and deionized water, and then dried to obtain a precursor powder, and finally the precursor powder is sintered in an air atmosphere. When the porous Fe2O3@Mn2O3 core-shell cubic structure material prepared by the present invention is used as a negative electrode active material for a lithium ion battery, it exhibits the characteristics of high capacity, good rate performance and good cycle stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion battery electrode materials, and specifically relates to a porous Fe 2 O 3 @Mn 2 O 3 Core-shell cubic structure material and preparation method thereof. Background Art

[0002] Lithium-ion batteries are gradually gaining attention in the energy storage industry due to their environmental friendliness, long life, no memory effect, and high energy density. However, the current commercial graphite anodes have disadvantages such as low theoretical specific capacity, unsafe embedding potential, slow electrochemical kinetics, and poor rate performance, which cannot meet the growing energy demand of the energy storage industry, especially their working potential (0.1 V vs. Li + / Li) may lead to "dead" lithium and lithium dendrites, resulting in rapid capacity decay and greatly reduced safety. Therefore, it is of great significance to develop new lithium-ion battery anodes with high specific capacity, safe working potential and rate performance. Metal oxides such as Fe 2 O 3 , Mn 2 O 3 Cr 2 O 3 etc. have become alternative options due to their high theoretical capacity and abundant resources. However, these materials have the disadvantages of large volume expansion, low intrinsic conductivity, irreversible structural collapse, uncontrollable particle aggregation, and slow electrochemical reaction kinetics, resulting in poor rate performance and cycle stability, which limits the improvement of the cycle life of lithium-ion batteries. Among the many strategies to solve the above problems, special morphology design and structural optimization are the most effective solutions.

[0003] Among various morphologies, porous core-shell structures are widely used to buffer the volume change of materials during battery cycling because of their adaptive characteristics to the tension caused by structural changes during battery cycling. On the other hand, heterogeneous structures can effectively exert the synergistic effect between the two materials to enable the material to obtain better electrochemical performance. The combination of the two strategies should be able to obtain materials that can buffer volume changes and have good electrochemical properties. In addition, Fe 2 O 3 The theoretical specific capacity is as high as 1007 mAh g -1 , Mn 2 O 3 It has a higher theoretical specific capacity (1018 mAhg -1), in addition, the two materials are very abundant in nature and cheap. More importantly, the redox potentials of the two materials are intertwined, which provides a buffer matrix for each other. Summary of the invention

[0004] The technical problem to be solved by the present invention is to propose a porous Fe 2 O 3 @Mn 2 O 3 Core-shell cubic structure material and preparation method thereof, the raw material for preparing the material is abundant in reserve, low in price, the production method is simple and safe, and the prepared porous Fe 2 O 3 @Mn 2 O 3 Core-shell cubic structure electrode materials have excellent electrochemical properties and can be used as negative electrode materials for lithium-ion batteries.

[0005] A porous Fe for lithium ion battery 2 O 3 @Mn 2 O 3 A method for preparing a core-shell cubic structure material, the preparation method comprising the following steps:

[0006] S1. 2 OH) 2 Add deionized water and stir evenly to obtain an ethylene glycol aqueous solution;

[0007] S2. Fe(NO 3 ) 3 9H 2 O, MnSO 4 ·H 2 O, CH 4 N 2 O is added into the ethylene glycol aqueous solution and stirred evenly;

[0008] S3. The mixed solution is poured into a micro high temperature autoclave and heated with stirring, and a hydrothermal reaction is performed;

[0009] S4. The mixed solution was taken out and cooled naturally to room temperature, and the resulting precipitate was washed several times by centrifugation with ethanol and deionized water, and then dried to obtain a precursor powder;

[0010] S5. Finally, the precursor powder is sintered in an air atmosphere to obtain porous Fe 2 O 3 @Mn 2 O 3 Core-shell cubic structure electrode materials.

[0011] The (CH 2 OH) 2 The volume ratio of 1:1 with deionized water;

[0012] The Fe(NO 3 ) 3 9H 2 O and MnSO 4 The molar ratio of H2O is 1:1; Fe(NO 3 ) 3 9H 2 O and CH 4 N 2 The molar ratio of O is 1:10;

[0013] The hydrothermal reaction temperature in S3 is 140-160° C., for example, 140, 150, 160° C.; the hydrothermal reaction time is 10 h, the stirring speed is 600 rpm, and the pressure is 3-4 MPa, for example, 3, 4 MPa;

[0014] The sintering temperature in S5 is 800°C, the temperature is kept for 4 h, and the heating rate is 20°C min -1 ;

[0015] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0016] The present invention uses a one-step hydrothermal method to produce a porous Fe 2 O 3 @Mn 2 O 3 Core-shell cubic structure material, with a particle size of 5-6 um and mesopores of 100-150 nm. The unique structure and mesopores increase the contact area between the electrode material and the electrolyte, shorten the diffusion distance of ions and electrons, and have enough free space to adapt to the volume change of the electrode material, thereby improving the cycle stability of the material to a certain extent. When used as a negative electrode active material for lithium-ion batteries, it exhibits the characteristics of high capacity, good rate performance and good cycle stability; Fe 2 O 3 and Mn 2 O 3 The two materials are directly in contact with each other in the micro region, which can give full play to the electrochemical properties of the materials and the synergistic effect between the two. Secondly, the raw materials used in the present invention are abundant in reserves, low in price, simple in process and easy to operate. The porous Fe 2 O 3 @Mn 2 O 3 The core-shell cubic structure electrode material precursor can be obtained by solid phase sintering in a dry and air atmosphere to obtain porous Fe2 O 3 @Mn 2 O 3 Core-shell cubic structure electrode materials.

[0017] The present invention has strong feasibility, is easy to scale up, conforms to the characteristics of green chemistry, and is conducive to market promotion. 2 O 3 @Mn 2 O 3 The method for producing core-shell cubic structure electrode materials is simple and easy to operate, the raw materials for production are abundant in reserves and low in price, and the prepared materials have high purity and uniform structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and should not be regarded as limiting the scope.

[0019] Image Captions

[0020] Figure 1 A porous Fe 2 O 3 @Mn 2 O 3 Schematic diagram of the preparation process of core-shell cubic structure materials;

[0021] Figure 2 The porous Fe for lithium ion battery in Example 1 2 O 3 @Mn 2 O 3 XRD pattern of core-shell cubic structure material;

[0022] Figure 3 (a) is porous Fe 2 O 3 @Mn 2 O 3 SEM of core-shell cubic structure material; Figure 3 (b) is the EDS result of Fe element; Figure 3 (c) is the EDS result of Mn element; Figure 3 (d) is the EDS result of O element;

[0023] Figure 4 The porous Fe for lithium ion battery in Example 1 2 O 3 @Mn 2 O 3 Battery rate diagram of core-shell cubic structure materials;

[0024] Figure 5 The porous Fe for lithium ion battery in Example 1 2 O 3 @Mn 2 O 3 Long cycle performance diagram of core-shell cubic structured materials;

[0025] Figure 6 The porous Fe for lithium ion battery of Example 1, Comparative Examples 1, 2, and 3 2 O 3 @Mn 2 O 3 Long cycle performance diagram of core-shell cubic structured materials. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical scheme and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all the embodiments.

[0027] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, those skilled in the art can select within a suitable range through the description of the text.

[0028] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0029] Example 1

[0030] A porous Fe for lithium ion battery 2 O 3 @Mn 2 O 3 Core-shell cubic structure material porous Fe 2 O 3 @Mn 2 O 3 The method for preparing a core-shell cubic structure material comprises the following steps:

[0031] (1) Mix 25 ml of ethylene glycol solution and 25 ml of deionized water in a ratio of 1:1 and heat and stir at 45°C for 2 min.

[0032] (2) Add 4 mmol Fe(NO 3 ) 3 9H 2 O, 4 mmol MnSO 2 ·H 2 O, 40 mmol CO(NH2 ) 2 Soluble in

[0033] The ethylene glycol aqueous solution prepared in step (1) was stirred in a water bath at 45°C for 30 min.

[0034] (3) After stirring evenly, the mixed solution was poured into a small stainless steel pressure reactor and heated and stirred. The hydrothermal reaction temperature was 150°C, the hydrothermal time was 10 h, the stirring speed was 600 rpm, and the pressure was 3 MPa.

[0035] (4) After the reaction is completed, the reaction product of the above reaction is taken out, and after cooling to room temperature, the obtained precipitate is centrifuged and washed several times with ethanol and deionized water, and then dried in an oven at 70° C. in an air atmosphere to obtain a precursor powder;

[0036] (5) Finally, the precursor was heated in air at 20 °C min -1 The porous Fe 2 O 3 @Mn 2 O 3 Core-shell cubic structure electrode materials.

[0037] The porous Fe 2 O 3 @Mn 2 O 3 Core-shell cubic structure material porous Fe 2 O 3 @Mn 2 O 3 Taking the core-shell cubic structure electrode material as an example, the experimental flow chart is as follows Figure 1 Its structure was determined by X-ray diffractometer. Figure 2 The X-ray diffraction pattern (XRD) shows that the porous Fe 2 O 3 @Mn 2 O 3 Core-shell cubic structure electrode material and card are JCPDS: 24-0072 Fe 2 O 3 and JCPDS: 31-0825 of Mn 2 O 3 The standard sample is consistent, indicating that the prepared porous Fe 2 O 3 @Mn 2 O 3 The core-shell cubic structure electrode material is indeed composed of two pure substances. Figure 3 The SEM and EDS images shown show that the produced porous Fe2 O 3 @Mn 2 O 3 The core-shell cubic structure electrode material has good structural stability.

[0038] The porous Fe 2 O 3 @Mn 2 O 3 The applications of core-shell cubic structure electrode materials as negative electrode active materials for lithium-ion batteries are as follows:

[0039] The production process of the negative electrode sheet adopts porous Fe 2 O 3 @Mn 2 O 3 The core-shell cubic structure electrode material is used as the active material, acetylene black is used as the conductive agent, 4% polyvinylidene fluoride (PVDF) is dissolved in an appropriate amount of N-methylpyrrolidone as a binder, and the mass ratio of active material, acetylene black, and carboxymethyl cellulose is 70:20:10; after the active material and acetylene black are fully mixed in proportion, a certain amount of N-methylpyrrolidone is added, and the mixture is evenly ground, and the resulting mixed solution is applied on the copper foil. The coated electrode sheet is placed in an oven at 70°C and dried for 24 hours, then taken out and made into an electrode sheet with a diameter of 14 mm for use. With 1M lithium hexafluorophosphate (LiPF 6 ) is dissolved in ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1 as an electrolyte, a lithium sheet is used as a negative electrode, a Celgard 2500 microporous polypropylene membrane is used as a separator, and CR2023 stainless steel is used as a battery shell to assemble a button-type lithium-ion battery. The remaining steps of the lithium-ion battery production method are the same as the usual production method.

[0040] Attached Figure 4 The porous Fe 2 O 3 @Mn 2 O 3 The rate performance of the core-shell cubic structure electrode material at different current densities. -1 , 200 mA g -1 , 500 mA g -1 , 1000 mA g -1 and 2000 mA g -1 At a current density of 2 O 3 @Mn 2 O 3 The discharge capacity of the core-shell cubic structure electrode material can reach 1073.4 mAh g -1、857.9 mAhg -1 、722.2 mAh g -1 、606.2 mAh g -1 , 426.9 mAh g -1 The material has excellent rate performance, and can -1 After charge and discharge cycles at different current densities, when the current density returns to 500 mA g -1 The capacity can be restored to 730.5 mAh g -1 When the current density returns to 100 mA g -1 The capacity can be restored to 997.5 mAh g -1 , indicating that the material has good structural stability.

[0041] From the attached Figure 5 It can be seen that the cycling stability of the material is also very outstanding. -1 At a current density of 1.5 Å, the discharge capacity can still maintain 77.6% after 300 cycles. The above performance shows that porous Fe 2 O 3 @Mn 2 O 3 The core-shell cubic structure electrode material has very excellent electrochemical properties and is a potential negative electrode material for lithium-ion batteries.

[0042] Comparative Example 1

[0043] The only difference between this comparative example and Example 1 is that the hydrothermal reaction temperature is 140° C., and the other conditions and parameters are exactly the same as those in Example 1.

[0044] Comparative Example 2

[0045] The only difference between this comparative example and Example 1 is that the hydrothermal reaction temperature is 160° C., and the other conditions and parameters are exactly the same as those in Example 1.

[0046] Comparative Example 3

[0047] The only difference between this comparative example and Example 1 is that the hydrothermal reaction pressure is 4 MPa, and the other conditions and parameters are exactly the same as those in Example 1.

[0048] Results Analysis

[0049] Table 1 is the results of the embodiments of the present invention and the comparative examples.

[0050]

[0051] From Table 1 and Figure 6 It can be seen from Example 1 that the porous Fe2 O 3 @Mn 2 O 3 Batteries made of core-shell cubic structure materials have high discharge capacity and capacity retention rate. -1 At a current density of 1.3 mAh g, the discharge capacity of Example 1 is the highest, which is 760.3 mAh g -1 The capacity retention rate after 300 cycles is 77.6%, which is the best performance. The second is comparative example 1, with a discharge capacity of 729.2 and a capacity retention rate of 65.2% after 300 cycles. The discharge capacity of comparative example 3 is the lowest, which is 562.1 mAh g -1 , the capacity retention rate is 31.4% after 300 cycles, while the performance of Comparative Example 2 is between Comparative Example 1 and Comparative Example 3, with a higher discharge capacity and a lower capacity retention rate.

[0052] The above contents are further detailed descriptions of the present invention in combination with specific / preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. Without departing from the concept of the present invention, it is also possible to make several substitutions or modifications to these described embodiments, and these substitutions or modifications should be deemed to belong to the protection scope of the present invention.

Claims

1. A method for preparing a porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries, characterized in that: The following steps are involved: S1. Add (CH2OH)2 to deionized water and stir to obtain an ethylene glycol aqueous solution; S2. Add Fe(NO3)3·9H2O, MnSO4·H2O, CH4N2O into ethylene glycol aqueous solution and stir evenly; S3. The mixed solution is poured into a micro high temperature autoclave and heated with stirring, and a hydrothermal reaction is performed; S4. The mixed solution was taken out and cooled naturally to room temperature, and the resulting precipitate was washed several times by centrifugation with ethanol and deionized water, and then dried to obtain a precursor powder; S5. Finally, the precursor powder is sintered in an air atmosphere to obtain a porous Fe2O3@Mn2O3 core-shell cubic structure electrode material; The volume ratio of (CH2OH)2 and deionized water in S1 is 1:1; The molar ratio of Fe(NO3)3·9H2O to MnSO4·H2O in the S2 is 1:1; the molar ratio of Fe(NO3)3·9H2O to CH4N2O is 1:10; The hydrothermal reaction temperature in S3 is 140-160° C., the hydrothermal reaction time is 10 h, the stirring speed is 600 rpm, and the pressure is 3-4 MPa; The sintering temperature in S5 is 800°C, the temperature is kept for 4 h, and the heating rate is 20°C min -1 .

2. A porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries, characterized in that: The preparation method according to claim 1 is adopted.

3. The porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries according to claim 2, characterized in that: The porous Fe2O3@Mn2O3 core-shell cubic structure material has a particle size of 5-6 um and mesopores of 100-150 nm.

4. The porous Fe2O3@Mn2O3 core-shell cubic structure material for lithium-ion batteries according to claim 2, characterized in that: at 100 mA g -1 , 200 mA g -1 , 500 mA g -1 , 1000 mA g -1 and 2000 mA g -1 At a current density of 1.34 Å, the discharge specific capacities of the porous Fe2O3@Mn2O3 core-shell cubic structure electrode materials are 1073.4 mAh g -1 、857.9 mAh g -1 、722.2 mAh g -1 、606.2 mAh g -1 , 426.9 mAh g -1 ; After 100 - 2000 mA g -1 After charge and discharge cycles at different current densities, when the current density returns to 500 mA g -1 When the capacity is restored to 735 mAh g -1 When the current density returns to 100 mA g -1 The capacity is restored to 995 mAh g -1 ; at 1000 mA g -1 At a current density of , the capacity retention rate after 300 cycles is 76%.

Citation Information

Patent Citations

  • Process for production of active material and electrode, active material, and electrode

    CN101127399A

  • Method for preparing nanocomposite of MnO2 / C / Fe2O3 layer-upon-layer structure

    CN104851597A